Structure and catalytic properties of sulfated zirconia foams - Alves-Rosa, Marinalva A. [UNESP]; Martins, Leandro [UNESP]; Hammer, Peter [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Springer, 2014)
Porous sulfated zirconia foams were manufactured by a simple methodology based on the sol-gel process combined with a liquid foam template that used a surfactant mixture. A block copolymer (Pluronic F-127) and an anionic surfactant [sodium dodecylsulfate (SDS)] were mixed in different proportions in order to optimize the porous and surface properties of the ceramic material. By adjusting the SDS/Pluronic ratio, it was possible to obtain sulfated zirconia with a combination of macropores and mesopores that provided high porosity (a parts per thousand 90 %) and surface area (a parts per thousand 80 m(2) g(-1)). The sulfate groups linked to the zirconia surface stabilized the tetragonal phase, to the detriment of the thermodynamically stable monoclinic phase. The sulfate groups and the tetragonal phase decreased as a function of the amount of SDS in the liquid foam template. The combined porous and structural characteristics, together with surface acidity, provided enhanced catalytic activity when the sulfated zirconia foams were employed in the isopropanol dehydration reaction. A further benefit was the selectivity towards propene and negligible formation of acetone.
Keywords: Sulfated zirconia; Porous ceramic; Surfactants mixture; Sol-gel; Catalytic isopropanol dehydration